Radiographic study of mental foramen in Chitwan population - Thakur, Smriti Narayan; Mishra, Meena Kumari; Pandey, Basuraj; Singh, Harendra; Mishra, Shrijana (Journal of Chitwan Medical College, 2019)
Background: Knowledge about the type & position of mental foramen is very much important landmark for dentists to perform any surgical procedure in the vicinity of mental foramen. The purpose of this study was to determine the most frequently occurring type & position of the mental foramen in Chitwan population using digital Panoramic Radiograph. Methods: This cross-sectional retrospective study was conducted on 500 (250 Male& 250 Female) digital panoramic radiograph which were collected from the department of Oral Medicine & Radiology. The type & position of Mental Foramen was analysed with Dicom viewer. The data obtained was statistically analyzed by with descriptive and inferential statistics using SPSS Version 20. Result: The most common type of mental foramen was Type 3 (diffuse with a distinct border of the foramen) & the test showed significant difference by gender. The most common position of mental foramen was position 4 (in line with second premolar) followed by position 3 (Between the first & second premolar) with no significant difference with gender with p-value <0.05. Conclusions: This study shows that the most frequent appearance of mental foramen lies in the line of second premolar. So this finding is used as a guide line in Chitwan population to perform various type of dental surgical procedure safely in mental foramen region but the accurate radiographic identification of mental foramen is paramount.